2022
DOI: 10.3389/fnhum.2022.819232
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pedaling at Different Cadence on Attentional Resources

Abstract: We investigated the relationship between attentional resources and pedaling cadence using electroencephalography (EEG) to measure P300 amplitudes and latencies. Twenty-five healthy volunteers performed the oddball task while pedaling on a stationary bike or relaxing (i.e., no pedaling). We set them four conditions, namely, (1) performing only the oddball task (i.e., control), (2) performing the oddball task while pedaling at optimal cadence (i.e., optimal), (3) performing the oddball task while pedaling faster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Although in our task saccades were not necessary only for smooth locomotion, it is likely that their occurrence helps to orient the body in an uncertain environment to guide locomotion. Indeed, we observed an increased modulation in the strength of saccade onset probability when walking slowly -a task which is known to place additional demands on sensory and cognitive systems (Akaiwa et al, 2022;Al-Yahya et al, 2011;Lajoie et al, 2016). Future research may further increase sensory uncertainty to investigate these modulations in saccade onset probability.…”
Section: Saccade Onsets Entrain To the Rhythm Of Footfallmentioning
confidence: 72%
“…Although in our task saccades were not necessary only for smooth locomotion, it is likely that their occurrence helps to orient the body in an uncertain environment to guide locomotion. Indeed, we observed an increased modulation in the strength of saccade onset probability when walking slowly -a task which is known to place additional demands on sensory and cognitive systems (Akaiwa et al, 2022;Al-Yahya et al, 2011;Lajoie et al, 2016). Future research may further increase sensory uncertainty to investigate these modulations in saccade onset probability.…”
Section: Saccade Onsets Entrain To the Rhythm Of Footfallmentioning
confidence: 72%
“…The electrooculogram (EOG) was recorded from the right suborbital region. Trials with EOG waveform exceeding 80 ÎŒV were rejected ( Akaiwa et al, 2022a ). EEG signals were recorded with a 0.1–200 Hz band-pass filter at a sampling rate of 1,000 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…As the most commonly used paradigms included free walking, this may be a relevant factor that modulates the effect of simultaneous motor activity on the P300 in an oddball paradigm. In fact, the majority of studies with negative effects were free (outdoor) walking studies [ N = 4 ( Debener et al, 2012 ; De Vos et al, 2014 ; Reiser et al, 2019 ; Scanlon et al, 2020 )], two other walking studies used a treadmill ( Shaw et al, 2018 ; Cortney Bradford et al, 2019 ) and the remaining two were pedaling studies [visual: Yagi et al (1999) , tactile: Akaiwa et al (2022) ]. Most active conditions lasted for 10 min at maximum, except for Akaiwa et al (2022) , where one condition lasted about 15 min, and Cortney Bradford et al (2019) and Reiser et al (2019) where subjects walked on a treadmill for 1 h. All of the studies with negative effects on attention reported a decreased P300 amplitude in response to the locomotion condition as compared to the sitting or standing conditions.…”
Section: Methodsmentioning
confidence: 99%